A study of acoustic emissions signal events in pedicle screw fixation procedure - Mohd Hizzuan, Harun (2009)
The purpose of this study is to propose a safe and easy method to help medical practitioner for perforation of hole during pedicle screw fixation procedure by using acoustic emissions technique. Generally in Malaysia, the medical practitioner had a really hard time while doing the pedicle screw fixation procedure when it involved with cervical spine. The cervical spine is the most complicated articular system in the body. The pedicles of the cervical spine are short and thick and become the most critical part during the screw insertion process. For this study, two cervical bovine vertebras were used instead of human vertebrae. The source of the acoustic emissions (AE) signal events was from the breakthrough of the bone tissues and it is was captured using AE sensor with the help of Acoustic Emission Detector Software version 2.1.3. Acoustic emissions signal events showed the different trend in hits results when the signal run through the bone tissues either hard of spongy during the perforation of the bone. By the experiment on the first bone, there were sudden increase of hits occur that tell us the pedicle probe had been breakthrough the interface between the hard and soft bone tissues. Meanwhile, in the experiment on the second bone an indicator is used to estimate the time of penetration level where the crack propagation of the bone tissues interfaces occur and the result showed the time were vary for each hole.